2017
DOI: 10.1111/bjep.12170
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to arithmetic fact retrieval and percentage calculation in adolescents

Abstract: There are both similarities and differences in the cognitive mechanisms underlying arithmetic fact retrieval and percentage calculation in adolescents. Adolescents' symbolic-number processing, arithmetic fact retrieval, and percentage calculation continue to rely on the linguistic pathways, whereas the reliance upon the spatial pathway has ceased. The reliance upon the quantitative pathway varies depending on the task.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…According to the Cattell–Horn–Carroll (CHC) theory of cognitive abilities, processing speed typically includes: perceptual speed, decision speed, arithmetic fluency, and reading fluency ( Schneider and Mcgrew 2012 ). Several existing studies reported that processing speed is associated with children’s mathematical achievement ( Bull and Johnston 1997 ; Cowan et al 2011 ; Fuchs et al 2006 ; Fung et al 2014 ; Geary 2011 ; Hecht et al 2001 ; Lambert and Spinath 2017 ; Leikin et al 2014 ; Lin 2020 ; Passolunghi and Lanfranchi 2012 ; Rohde and Thompson 2007 ; Taub et al 2008 ; Träff et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Cattell–Horn–Carroll (CHC) theory of cognitive abilities, processing speed typically includes: perceptual speed, decision speed, arithmetic fluency, and reading fluency ( Schneider and Mcgrew 2012 ). Several existing studies reported that processing speed is associated with children’s mathematical achievement ( Bull and Johnston 1997 ; Cowan et al 2011 ; Fuchs et al 2006 ; Fung et al 2014 ; Geary 2011 ; Hecht et al 2001 ; Lambert and Spinath 2017 ; Leikin et al 2014 ; Lin 2020 ; Passolunghi and Lanfranchi 2012 ; Rohde and Thompson 2007 ; Taub et al 2008 ; Träff et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“… Rohde and Thompson ( 2007 ) reported that processing speed, which is assessed by symbolic visual matching—letters and numbers stimuli, constantly accounted for a significant amount of additional variance in mathematics performance. Additionally, processing speed could also predict mathematic achievement longitudinally ( Cowan et al 2011 ; Geary 2011 ; Passolunghi and Lanfranchi 2012 ; Träff et al 2017 ). Path analyses models revealed the following findings about processing speed: (1) prediction power of number symbolic visual matching for numerical competence among pre-schoolers, and (2) prediction power for mathematical achievement among followed-up first graders ( Passolunghi and Lanfranchi 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous research as described above, we expected basic numerical abilities to predict time reading in general significantly. In particular, addition (reflecting magnitude manipulation) and arithmetic fact knowledge (e.g., multiplication) were shown to be significant predictors of mathematical achievement in general (e.g., Geary, Nicholas, Li, & Sun, 2017;Jordan, Hanich, & Kaplan, 2003;Krajewski & Schneider, 2009;Träff, Skagerlund, Olsson, & Östergren, 2017) and digital time reading but also to a lesser extent analog time reading in particular (e.g., Friedman & Laycock, 1989). Even tough studies are missing, it seems reasonable that subtraction skills also reflecting magnitude manipulation (e.g., Dehaene & Cohen, 1997) should also be a relevant predictor of time reading in general.…”
Section: Introductionmentioning
confidence: 99%
“…This test was developed by the first author and has been used in a number of studies on children aged 6–15 years (e.g., Träff et al, 2017a,b,c). The child was presented with sequences of words read by the experimenter, spanning from a minimum of two words to a maximum of seven words.…”
Section: Methodsmentioning
confidence: 99%